Draft Annual Plan 2010-2011 Orissa Volume-I - Planning Commission (Planning Commission, 2010)
Orissa, located on the east coast, is flanked by West Bengal and Jharkhand in North, Jharkhand and Chhatisgarh in West and Andhra Pradesh in South. It has more than 480 km long coastline. It is the 9th largest State with an area of 155,707 km2, and 11th largest in terms of population with 36.80 million people as per 2001 census. It is 14,h with regard to population density with 236 persons per km2 in 2001. It contributes about 2% of the national income. Its decadal population growth rate (16.25% in 1991-01) is lower than the national average, though there are wide inter-district variations. As per 2001 census, Scheduled Castes and Scheduled Tribes respectively constitute 16.56% and 22.13% of total population. Its sex ratio has marginally improved from 971 in 1991 to 972 in 2001 and is better than the national average.
Government of Orissa Planning & Co-Ordination Department Bhubaneswar